Pleomorphic Adenoma of the Parotid Gland: A Case Report - Rajesh Gupta; Preety Gupta; Shivani Gupta; Sumit Garg (International Healthcare Research Journal, 2021)
Salivary organ tumors are uncommon, including under 3 % of all neoplasia of head and neck district. Pleomorphic adenoma is the most well-known salivary organ tumor, representing 60-80% of amiable tumors of salivary organs. Generally they are found as singular one-sided, firm and portable, effortless, moderate developing mass. The board includes careful resection by shallow or absolute parotidectomy.